Isotretinoin induces dermcidin expression in patients with moderate to severe acne vulgaris - Magdy A.A Ragab; Salma S Omar; Reham A.H Abo El-Wafa; Eman A Sultan; Neveen R Gomaa (Wolters Kluwer Medknow Publications, 2019)
Background The continuous low-dose (LD) isotretinoin is a frequently used treatment regimen for acne vulgaris. However, data about its antimicrobial efficacy are lacking. Objective To study dermcidin expression and the effects of LD and conventional-dose isotretinoin (CD) on its expression in patients with moderate-severe acne vulgaris. Patients and methods Skin dermcidin expression was investigated in 30 patients with moderate-severe acne vulgaris and 15 healthy control patients using ELISA. In this case-control study, 15 patients were given continuous LD isotretinoin (0.3 mg/kg/day), and the other 15 were given the conventional high dose (0.5 mg/kg/day). Skin biopsies were taken at the start of the study and 6 months after. Results Dermcidin was significantly lower in patients with acne vulgaris (P<0.001). Both isotretinoin regimens significantly raised dermcidin levels compared with pretreatment values (P<0.001). Relapse after 12 months was not statistically different between the two isotretinoin regimens (P=0.464). In the LD group, the pretreatment global acne grading system score of 29±6.6 decreased to a score of 5.7±6.5 after treatment (P=0.045). In the CD, the pretreatment score of 28±6.5 decreased to 6±5.9 after treatment (P=0.032). Relapses after 12 months were significantly related to post-treatment dermcidin levels in both of the LD (P=0.027) and CD (P=0.008) groups. Conclusion Dermcidin expression is reduced in acne vulgaris. CD and LD isotretinoin regimens are associated with increased dermcidin expression.